KOMUNIKASI PEMASARAN TERPADU UNTUK NICHE MARKET PADA SAYUR BOX DI MASA PANDEMI - Umar, Umar (Interaksi: Jurnal Ilmu Komunikasi, 2022)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are increasing. As technology develops, MSMEs are forced to adapt and integrate. Facing such competition and challenges amidst the COVID-19 pandemi, MSMEs need to target market niches by conducting integrated marketing. This research was conducted on Sayur Box as an MSME that utilizes the niche market well. With a qualitative approach and descriptive-explorative research type, this research uses content analysis method. The results show that the success of Sayur Box’s niche market is due to brand adoption by implementing compatibility and observability. Some of the integrated marketing communication elements developed by Sayur Box are communication tools, messages, brands, technology and relationships. In an integrated marketing communication effort, Sayur Box utilizes social media, websites and blogs to interact with consumers. Sayur Box has fulfilled eleven primary categories, according to the results of content analysis classification on @sayurbox Instagram posts.